Review on awareness and practices in Malaysia land-use planning on municipal solid waste management - Khairunnisa Syarafina Samsudin,; Sohif Mat,; Halim Razalia,; Noor Ezlin Ahmad Basri,; Zulkifli Aini, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In 2016, almost 95% of the collected waste were taken to about 156 treatment disposal facilities that are distributed throughout Peninsular Malaysia, yet municipal solid waste (MSW) open dumping is common wherever land is available. Previous studies show that the land-use activities influenced the waste generation. The issue of non-compliance such as illegal change of land-use zoning and conflicts in development plans are among others that affect environmental sustainability. Hence, this paper focuses on how land-use planners include MSW management (MSWM) in their development planning. As a case study, the research considers 30 government town planners and 30 registered town planning consultants with the Malaysian Institute of Planners. A close-ended questionnaire method was adopted in this research. To design the questions, three aspects were considered: technical, management, and behaviour and the questions were structured based on literature review, books, and personal experience of the people involved. This research further identifies the issue concerning the reasons for the lack of involvement of land-use planners to include MSWM. Results show that land-use planners are aware of the regulations, national plans, and policies regarding MSWM in Malaysia but lack actions in their planning due to several reasons, such as inadequate expertise and insufficient funding. The findings in this research are expected to provide useful guidelines for policy makers.